Visuelle Dimensionen des Antiziganismus - Reuter, Frank; Gress, Daniela; Mladenova, Radmila (Antiziganismusforschung interdisziplinär - Schriftenreihe der Forschungsstelle Antiziganismus, 2021)
Visual media have played a key role in the genesis of antigypsyism since the early modern period. This interdisciplinary anthology examines the central motifs and semantics of "Gypsy" images in various forms of representation such as literature, visual art, photography, postcards, opera, theatre, comics, film and computer games. Particular attention is paid to connecting lines and interrelationships. The contributions uncover the content-related, temporal, geographical and media-specific manifestations of one of the most powerful stereotypes in European cultural history. To this day, antigypsyist imaginations have a negative impact on the positioning of Sinti and Roma in European societies.